Evaluation of the self-administration potential of high-density microarray patches to human skin: A preliminary study. Issue 1 (31st December 2023) - Baker, B.; Hacker, E.; Siller, G.; Lee, M.; Mursaliyev, N.; Forster, A.
ABSTRACT: The high-density microneedle array patch (HD-MAP) is a novel vaccine delivery system with potential for self-administered vaccination. In this study, Vaxxas HD-MAPs were applied by both a trained user and self-administered with application sites compared to determine the response of skin and the level of engagement of the HD-MAP with human skin. Twenty healthy participants were enrolled, and the response of skin including erythema was observed at all application sites and no difference was found between trained user or self-administered applications. The majority of participants (70%) preferred the deltoid upper arm application site for applying HD-MAPs. Fluorescent dermatoscope images confirmed HD-MAPs engaged the skin surface and scanning electron microscopy (SEM) image analysis exhibited similar delivery characteristics for the upper arm and forearm sites when applied by either a trained user or self-administered. This study showed that noninvasive methods including dermatoscopy and SEM image analysis were able to estimate the engagement of HD-MAPs with human skin. HD-MAP self-vaccination technology has a unique proposition in pandemic preparedness by alleviating the need for health-care workers to administer vaccines, however greater awareness and understanding of the potential of this technology is required. GRAPHICAL ABSTRACT: uf0001